Association between the distribution of Capercaillies Tetrao urogallus and road and track densities at a landscape scale in a national park. Issue 1 (3rd April 2022) - Summers, Ron W.; Golder, Phil; Wallace, Nicole; Munro, Ewan; Wilson, Jeremy D.
ABSTRACT: Capsule: The inherited pattern of roads and tracks, now primarily used by people for recreation in the Cairngorms National Park, was associated with a reduced presence of Capercaillie Tetrao urogallus signs in woodland. Aims: To examine if the distribution of Capercaillies in the Cairngorms National Park was associated with the density of roads and tracks that run through woods in the Park, having accounted for habitat variables that are known to affect the distribution of Capercaillies. Methods: In 2013, Capercaillie distribution, as assessed from signs of presence, and habitat variables in seven woods totalling 142 km 2 within the Cairngorms National Park were assessed along regularly spaced transects. Numbers of people walking, on bicycles, and in vehicles were counted on selected tracks, and the density of roads and tracks (a measure of human use) in 0.25 km 2 squares of woodland was obtained from maps. A logistic regression compared habitat variables and road and track densities in 0.25 km 2 squares of woodland where signs of Capercaillie were or were not found. Results: Greater road and track densities were associated with reduced likelihood of finding Capercaillie signs in woodland squares, but the track effect was associated only with the two woods that had the highest levels of use by people. Conclusion: In response to the landscape-scale, correlative evidence of disturbance to Capercaillies, a reduction in track density (a current mean of 2.3 km per km 2 of woodland) or modifying human usage of tracks are conservation management options. This presents a challenge for forest managers, public bodies, the tourism industry, and others who wish to promote visitor access to the countryside and also to protect rare and vulnerable wildlife.